Upaya Pembinaan Kemandirian Warga Binaan Lapas - Fajar Rina Sejati; Dian Pertiwi (Jurnal Informasi Pengabdian Masyarakat, 2025)
This activity was carried out by the Abdimas Team under the ADAI organization, through hybrid (offline and online) at the Class IIA Salemba Correctional Institution, Jakarta, with the aim of building the independence of inmates through strengthening soft skills and entrepreneurship. This program is designed to motivate inmates about the importance of entrepreneurship training, digital business, and understanding the importance of social media to increase knowledge. The methods used include delivering educational material, discussion and practice. The results of this activity show a significant increase in the development of soft skills and the development of moral ethics to improve the quality of life of inmates, such as communication, leadership, team work and time management.